Fostering an Organization and Culture for Perpetual Revolution - Ramana Murthy, N. V. (Indian Journal of Marketing, 2009)
The present day ’global village’ concept calls for sustained improvement in every sphere-productivity, quality, technology, creativity’ etc. Every organization big small, public or private should curb rigidity of structures. To start with, an opening case is given from a government organization where the ethos of revolutionary thinking was cultivated by direct contacts of the top management with innovative front-line workers. Afterwards some determinants of ’revolutionary change’ are discussed. Every entity must be included in the magnetic aura of change; this can be achieved for instance by building lateral relations through human values. Decentralization is fundamental for unleashing imaginative approaches by all strata of employees since every individual is unique. It is imperative that process cycle time is minimized in every venture. Concurrently process capability has to be improved by vigorously implementing TQM. A sense of optimism that ’failures are building blocks to future triumphant success’ must pervade the human effort. Full-fledged empowerment needs practice by all leaders through ’self-efficacy, self-determination and impact’ culminating in self-empowerment by all people. The applications of reengineering are also discussed. Finally the yogic vision of seeing radiant light even in darkness is emphasized for achieving revolutionary improvements.